2019
DOI: 10.1123/ijspp.2018-0458
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine and Sprint Cycling Performance: Effects of Torque Factor and Sprint Duration

Abstract: The results of this study show that when torque factor and sprint duration are optimized, to allow participants to express their highest PPO, there is a clear effect of caffeine on sprinting performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…However, acute CAF ingestion significantly increased LA values at the post-test compared to PLA but this difference was not apparent after consumption of 1 week placebo, 3 or 6 mg/kg of CAF One of two main findings of current study is FIRSTCAF significantly improved sprint performance prior to 1 week of consumption period. Although anhydrous form of CAF was shown to be ergogenic on sprint performance by numerous studies (Dominguez et al, 2021;Glaister et al, 2019;Mohr et al, 2011), current study is first to found 6 mg/kg caffeinated coffee enhanced sprint performance compared to decaffeinated coffee as a placebo. Due to the methodological difficulties, coffee could not compared with anhydrous form but it is known that both coffee and anhydrous form improves resistance (Richardson et al, 2016) and endurance (Hodgson et al, 2013) exercise performance.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…However, acute CAF ingestion significantly increased LA values at the post-test compared to PLA but this difference was not apparent after consumption of 1 week placebo, 3 or 6 mg/kg of CAF One of two main findings of current study is FIRSTCAF significantly improved sprint performance prior to 1 week of consumption period. Although anhydrous form of CAF was shown to be ergogenic on sprint performance by numerous studies (Dominguez et al, 2021;Glaister et al, 2019;Mohr et al, 2011), current study is first to found 6 mg/kg caffeinated coffee enhanced sprint performance compared to decaffeinated coffee as a placebo. Due to the methodological difficulties, coffee could not compared with anhydrous form but it is known that both coffee and anhydrous form improves resistance (Richardson et al, 2016) and endurance (Hodgson et al, 2013) exercise performance.…”
Section: Discussionmentioning
confidence: 72%
“…Of these, caffeine (CAF) is most commonly administered prior to and during a game (Tallis et al, 2021). The acute intake of CAF doses of 3-6 mg/kg of body mass has been well established to improve performance in various exercise modalities including aerobic (Southward et al, 2018), anaerobic activities (Davis and Green, 2009), muscle performance such as strength (Grgic et al, 2020), muscular endurance (Flip-Stachnik et al, 2021), maximum power (Dominguez et al, 2021) and intermittent sprint performance (Mohr et al, 2011;Glaister et al, 2019). On the other hand, it has been still reported to be ineffective on some performance parameters (Clarke et al, 2016;Trexler et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Athletes visited the laboratory at least ±2 hr post-prandial. They were instructed to report to each test session in well-hydrated state, not to exercise the day before the test trials and to abstain from the caffeine intake for 3 hr prior to each test (Glaister et al, 2015(Glaister et al, , 2019Greer et al, 1998;Grgic, 2018). Muscle fatigue and vigorous PA may affect balance control; therefore, balance test did not take place after training and athletes who were engaged in vigorous PA excluded from the study (Barbieri et al, 2013).…”
Section: Data Collection Procedures Instruments and Measuresmentioning
confidence: 99%
“…PPO usually occurs a few seconds after a sprint is initiated (de Jong et al, 2015; Glaister et al, 2019; Wittekind et al, 2011), with power output declining thereafter. The optimal sprinting strategy has, therefore, been described as using an all-out approach (Abbiss & Laursen, 2008).…”
mentioning
confidence: 99%
“…There is, however, evidence to suggest that pacing does still exist during single (de Jong et al, 2015; Glaister et al, 2019; Wittekind et al, 2011) and repeated sprints (Billaut et al, 2011). During single sprints, even though the time to PPO was unaltered, a lower PPO has been found when longer sprints were undertaken (de Jong et al, 2015; Glaister et al, 2019; Wittekind et al, 2011). During repeated sprints, in comparison to a controlled trial, where the participants were correctly informed that they would be required to perform ten 6 s sprints with 24 s of recovery, power output was significantly higher during the first sprint, as well as the cumulated work over the first five sprints, in the deception trial, where the participants believed that they were only going to perform five sprints (Billaut et al, 2011).…”
mentioning
confidence: 99%